2022
DOI: 10.3390/biomedicines10112864
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence in Neurological Diseases—Is There Enough Evidence?

Abstract: The aging of the immune system has recently attracted a lot of attention. Immune senescence describes changes that the immune system undergoes over time. The importance of immune senescence in neurological diseases is increasingly discussed. For this review, we considered studies that investigated cellular changes in the aging immune system and in neurological disease. Twenty-six studies were included in our analysis (for the following diseases: multiple sclerosis, stroke, Parkinson’s disease, and dementia). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Additionally, there is a general decline in immune function and an increased predisposition to a proinflammatory state ( 28 ). The available evidence indicates that this phenomenon may be expedited in pwMS, leading to a higher proportion of memory CD4 T cells and impaired regulation via immune-checkpoint mechanisms ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is a general decline in immune function and an increased predisposition to a proinflammatory state ( 28 ). The available evidence indicates that this phenomenon may be expedited in pwMS, leading to a higher proportion of memory CD4 T cells and impaired regulation via immune-checkpoint mechanisms ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The natural aging of the immune system, known as "immunosenescence", could be responsible for the shift in MS from an inflammatory to a neurodegenerative nature (60). As we age, the innate and adaptive immune systems undergo numerous changes, including decreased pool of naïve T cells, decreased diversity in T-cell and B-cell receptors, age-related changes in B cell development and function, and accumulation of memory T cells (61,62).…”
Section: Underlying Pathophysiologymentioning
confidence: 99%
“…Normal aging decreases the brain's viability and increases its vulnerability to damage, 128,129 but neuronal loss is not a salient feature. [130][131][132] Instead, careful stereological studies have concluded that age-related changes in the central nervous system (CNS) in the cognitively intact, aging brain include alterations to neuron extensions (e.g., retraction of dendritic arbors and synapses); 133,134 deterioration of non-neuronal cells (e.g., oligodendrocytes, astrocytes, microglia); [135][136][137][138] and biochemical and molecular changes (e.g., reduced efficacy of neurotransmitters). [139][140][141][142] These effects of aging in the healthy brain differ from those seen with pathological aging due to neurological conditions such as Alzheimer's disease.…”
Section: Postmortem Neuropathologymentioning
confidence: 99%